Pipa filtrasi dalam mengurangi kadar zat kimia - Rohmah, Pujiati (Maliki Interdisciplinary Journal, 2023)
This paper seeks to provide solutions to various environmental problems in the surrounding environment. The need for awareness of every human being as a resident of the earth to maintain and care for the earth that is getting old, giving good treatment to fellow living creatures. When the earth is treated well by the inhabitants, they will also give good rewards to the inhabitants. Various natural disasters have occurred on earth, ranging from floods, landslides, even the supply of clean water is increasingly scarce. With this filtration pipe, being able to filter out chemicals in the water purification process, can help overcome existing water pollution problems. In the filtration pipe, natural ingredients are also arranged that are able to filter out chemical levels, so that the remaining filtered water can be reused. Even though in comparison there are more oceans than land, it is still the duty of earthlings to preserve and protect it.